Bioactive Compounds from Acrotrema arnottianum - Mathew, Joseph; George, V. (Asian Journal of Chemistry, 2010)
Lupeol, lupeol acetate, n-dotriacontanol, β-sitosterol and n-triacontanoic acid have been isolated and characterized from hexane extract and kaempferol, quercetin, 3-methoxy-4- hydroxy benzoic acid, quercetin-3-O-β-D-rhamnoside and kaempferol-4´-O-β- glucopyranoside have been identified from the methanol extract of Acrotrema arnottianum (whole plant). Antioxidant activity of the isolated compounds was studied by inhibition of lipid peroxidation in liver homogenate of adult male Wistar rats induced by Fe2+/ascorbate system and quantified spectrometrically. Antimicrobial activity of the extracts and isolates have been studied by disc diffusion technique.